Analysis of the Impact of Earnings Management and Sustainability Report on Tax Aggressiveness - Winanto, Rando; Armazy, Tejan Dayyan; Serawati, Silvi; Pahala, Indra; Wahono, Puji (International Journal of Business, Law, and Education, 2024)
This study aims to identify the impact of Earnings Management and Sustainability Report on Tax Aggressiveness. The research method used in this study is quantitative. The subjects in this study used a sample of 3 (three) manufacturing companies that have been registered and licensed on the Indonesia Stock Exchange. The data collection method uses sustainability report records and annual financial reports uploaded to the Indonesia Stock Exchange and sustainability reports that can be downloaded from the company's website for the 2018-20 22 analysis period. The data analysis method used in this study is the regression test using SPSS Version 22 to process and analyze the data. The value of the Earning Management variable (X 1 ) has a T value of 4.505 and is greater than the 5% significance value of 2.178. In addition, the test on the Earning Management variable (X 1 ) shows a value of -4.505. This indicates that an increase in earnings management efficiency can significantly decrease Tax Aggressiveness by 450.5%. However, the Sustainability Report (X 2 ) does not significantly affect Tax Aggressiveness with a test value of 0.313 smaller than the 5% significance value of 2.178, indicating that for every 1% increase in Sustainability Report, there is a 31.3% increase in the value of Tax Aggressiveness.